2018
DOI: 10.4103/ijpsym.ijpsym_244_17
|View full text |Cite
|
Sign up to set email alerts
|

The Clock Drawing Test versus Mini-mental Status Examination as a Screening Tool for Dementia: A Clinical Comparison

Abstract: There is a growing incidence of dementia patients in the community, and with this growth, there is need for rapid, valid, and easily administrable tests for the screening of dementia and mild cognitive impairment in the community. This review looks at the two most commonly used tests in dementia screening, namely, the clock drawing test (CDT) and the mini-mental status examination (MMSE). Both these tests have been used in dementia screening over the past three decades and have been the subject of scrutiny of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 95 publications
0
48
0
1
Order By: Relevance
“…Originally, the CDT was developed as an instrument for attentional and visual disorders [128, 129]. Due to its valuable characteristics (i.e., free of charge, quick, easy to administer, relatively high robustness), the CDT has gained in popularity among practitioners and researchers as a screening instrument for Alzheimer's dementia either by itself or as part of a test battery [130137]. Because of its simplicity and brevity, the CDT is well accepted by older and very old adults [138].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Originally, the CDT was developed as an instrument for attentional and visual disorders [128, 129]. Due to its valuable characteristics (i.e., free of charge, quick, easy to administer, relatively high robustness), the CDT has gained in popularity among practitioners and researchers as a screening instrument for Alzheimer's dementia either by itself or as part of a test battery [130137]. Because of its simplicity and brevity, the CDT is well accepted by older and very old adults [138].…”
Section: Resultsmentioning
confidence: 99%
“…In clinical practice, there are basically three approaches on how to administer the CDT. The most common administration instructions ask the patient to draw a clock face with all its numbers and set the time to 10 past 11 [137]. Variations can include a pre-drawn clock face, a different time setting, or a toy clock from which the patient needs to read the time [132, 141, 142].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clock-drawing test is one of the more conceptually simple of the cognitive tests in common use. Though there are a variety of scoring systems that have been applied to the test, they generally assign points to different elements of the clock, such as its shape, and how the numbers and clock hands are positioned [ 32 ]. The patient is assigned the task of drawing an analog clockface at a certain time, usually 11:10.…”
Section: Common Cognitive Assessmentsmentioning
confidence: 99%
“…Author of Paper [22] found that free-drawn CDT version is more cognitively demanding and sensitive for detecting mild/early cognitive impairment as against an incomplete-copy version where subjects were given a clock face with numbers and asked to copy the clock and set the hands for a specific time. Authors in the paper [15]…”
Section: Clock Drawing Test (Cdt)mentioning
confidence: 99%